Synthesis of five- and six-membered nitrogen and sulfur heterocyclic compounds - Borah, Madhurjya (My University, 2018)
The content of this thesis has been divided into five chapters based on the results of experiment work performed during the complete course of the research period. The chapter 1 of the thesis presents an introduction to nitrogen and sulfur heterocyclic compounds, their biological significance and the literature method for their synthesis. Chapter 2 describes a method for the diastereoselective synthesis of substituted tetrahydro-thiophenes and -thiopyrans via thia-Prins cyclization reaction. Chapter 3 deals with the diastereoselective synthesis of substituted morpholines from N-tethered alkenols and its application in total synthesis of (±)-chelonin A. In chapter 4, FeCl3-mediated carbenium-ion induced intramolecular cyclization of N-tethered alkyne-benzyl alkanols is described. Chapter 5 presents the synthesis of tetrahydroisoquinolines from N-tethered aryl-benzyl alkanols mediated by BF3.OEt2
Saikia, Anil Kumar
Keywords: CHEMISTRY